Karṇa : panca aṅkoṃ meṃ eka paurāṇika nāṭaka - Govindadāsa, 1896-1974 (SAMP early 20th-century Indian books project, 1946)
Play based on the life of Karṇa, a character from the Mahābhārata, Hindu epic.